The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/eji.201847586
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal epithelial cells and T cells differentially recognize and respond to Candida albicans yeast and hypha

Abstract: Inflammatory bowel diseases (IBD) are a multifactorial disorder. Our understanding of the role of bacteria in the pathogenesis of IBD has increased substantially; however, only scarce data exist regarding the role of commensal fungi in maintaining intestinal homeostasis and triggering IBD. Candida albicans (C. albicans) is a member of the intestinal mycobiome and proposed to contribute to IBD pathogenesis. We aimed to investigate the influence of the two morphologies of C. albicans, yeast and hypha, on epithel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…Indeed, the expression of MyD88, IRF3, IRF5, and TLR2 was significantly increased in BMECs infected by both the yeast phase and the hypha phase of C. krusei, while the expression of TLR4 was significantly increased by the C. krusei hypha phase. These findings are consistent with previous findings that both the yeast phase and the hypha phase of C. albicans can induce TLR2 and TLR4 upregulation in T cells and human intestinal epithelial cells [56]. It was speculated that both the yeast phase and hypha phase of C. krusei could activate TLR2 in BMECs through the MYD88-dependent signaling pathway, while the activation of TLR4 in BMECs through the MyD88-independent signaling pathway might also be triggered by the hypha phase.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, the expression of MyD88, IRF3, IRF5, and TLR2 was significantly increased in BMECs infected by both the yeast phase and the hypha phase of C. krusei, while the expression of TLR4 was significantly increased by the C. krusei hypha phase. These findings are consistent with previous findings that both the yeast phase and the hypha phase of C. albicans can induce TLR2 and TLR4 upregulation in T cells and human intestinal epithelial cells [56]. It was speculated that both the yeast phase and hypha phase of C. krusei could activate TLR2 in BMECs through the MYD88-dependent signaling pathway, while the activation of TLR4 in BMECs through the MyD88-independent signaling pathway might also be triggered by the hypha phase.…”
Section: Discussionsupporting
confidence: 92%
“…From an immunological perspective, the in vitro Ca – and EcN–enterocyte interaction models similar to those used in our study have been characterized in the literature. Schirbel et al showed that both yeast and hyphal forms of Ca induce the production of hBD-2 as well as the pro-inflammatory cytokines thymic stromal lymphopoietin, IL-6 and IL-8, in Caco-2 cells [ 36 ]. They also showed increased expression of immune recognition and chemokine receptors, including TLR2, TLR4 and CXCR1 [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Schirbel et al showed that both yeast and hyphal forms of Ca induce the production of hBD-2 as well as the pro-inflammatory cytokines thymic stromal lymphopoietin, IL-6 and IL-8, in Caco-2 cells [ 36 ]. They also showed increased expression of immune recognition and chemokine receptors, including TLR2, TLR4 and CXCR1 [ 36 ]. Ca was able to activate the NF-κB signaling pathway as well as the cFOS gene, which encodes a subunit of the heterodimeric transcription factor AP-1, reflecting an expected induction of a damage response by the infected enterocytes [ 32 ].…”
Section: Discussionmentioning
confidence: 99%